Pelatihan Pemanfaatan Limbah Organik Rumah Tangga menjadi Pupuk Cair untuk Kelompok PKK Desa Sidomukti Kabupaten Semarang - Eva Banowati; Hasyatur Razzaq; Firda Salya Mutiara; Siti Nur Azizah; Aisyah Nurul Hidayati (Universitas Negeri Semarang, 2025)
The training program on utilizing household organic waste into liquid fertilizer for the PKK group in Sidomukti Village aims to improve knowledge and skills in processing organic waste into economically valuable products. The methods used include socialization, practical demonstrations, production of liquid fertilizer using anaerobic fermentation, and harvesting and evaluation. The training results showed a 78% increase in participants' understanding of organic waste management and liquid fertilizer production techniques. The liquid fertilizer produced has good physical characteristics with a blackish-brown color, a tapai-like aroma, and a pH of 5.5-6.5. The program received positive responses with 92% of participants expressing satisfaction, 89% intending to implement organic waste management at home, and 78% interested in developing organic liquid fertilizer businesses. The follow-up program includes expansion to all hamlets in Sidomukti Village and development of a village-level organic waste collection system.